2013
DOI: 10.1002/pssa.201228477
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen influence on the electrical properties of sputtered InN thin films

Abstract: Phone: þ55 11 3091 6684, Fax: þ55 11 3031 2742The narrow indium nitride (InN) bandgap has generated great interest for applications such as high-efficiency solar cells, lightemitting diodes, laser diodes, and high-frequency transistors. The ability to fabricate both p-type and n-type InN is essential for the production of these devices; however, InN is naturally an n-type semiconductor. This work's main objective is to study the influence of the deposition process using nitrogen and hydrogen on the optical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This provides a significant advantage to III-nitride family for the optoelectronic device applications such as full-color light-emitting diodes and highly efficient multi-junction solar cells. 6,7 Significant progress has been made in the growth of hexagonal InN by different growth methods and among them, the most prominent methods are molecular beam epitaxy (MBE), [8][9][10][11][12][13] metal organic vapor phase epitaxy (MOVPE), 14 high-pressure chemical vapour deposition (HP-CVD), 15,16 sputtering, [17][18][19][20] migration enhanced afterglow, 21 and pulsed laser deposition. 22 InN has a relatively low decomposition temperature and possesses high nitrogen equilibrium vapor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…This provides a significant advantage to III-nitride family for the optoelectronic device applications such as full-color light-emitting diodes and highly efficient multi-junction solar cells. 6,7 Significant progress has been made in the growth of hexagonal InN by different growth methods and among them, the most prominent methods are molecular beam epitaxy (MBE), [8][9][10][11][12][13] metal organic vapor phase epitaxy (MOVPE), 14 high-pressure chemical vapour deposition (HP-CVD), 15,16 sputtering, [17][18][19][20] migration enhanced afterglow, 21 and pulsed laser deposition. 22 InN has a relatively low decomposition temperature and possesses high nitrogen equilibrium vapor pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been used to fabricate semipolar InN films, including radio-frequency plasma-assisted molecular beam epitaxy (RF-MBE), 16) metalorganic vapor phase epitaxy, 17) pulsed laser deposition, 18) and magnetron sputtering. 19) Although metal organic chemical-vapor deposition (MOCVD), and MBE have often been used in the growth of InN thin films, few studies have reported semipolar InN( 1013) grown directly on a LaAlO 3 substrate using RF-MOMBE. Compared with the MOCVD growth method, the RF-MOMBE technique generally has the advantage of a low growth temperature for epitaxial nitride films.…”
Section: Introductionmentioning
confidence: 99%